Business Cycles, the Current Account, and Administered Protection in Mexico - Joseph Francois; Gunnar Niels (Tinbergen Institute, 2003)
Antidumping actions in the United States and EU are knownto be linked to macroeconomic conditions. In part, this is becausepositive injury findings may be easier to make in a downturn. Weexplore the evidence for Mexico, one of the main new antidumpingusing countries. Injury determination is also critica! in Mexico'santidumping policy, as a majority of unsuccessful complaints have beenrejected because of negative injury findings rather than negative findingsof dumping. Working with data from 1987 through 2000, we provideevidence for a relationship between macro-economic factors andantidumping complaints, including current account and exchange ratemovements, and both local and global general macroeconomicconditions.
Keywords: F10; F13; 330; antidumping; politica! economy of trade policy; Mexico.; Antidumping; Konjunktur; Leistungsbilanz; Mexiko